Formulation of a protein-free medium based on IPL-41 for the sustained growth of Drosophila melanogaster S2 cells - Batista, Fabiana R. X. (Springer Netherlands, 2008)
An animal protein-free medium was developed for Drosophila melanogaster S2 (S2AcGPV2) cells genetically modified to produce the rabies virus G glycoprotein (GPV). IPL-41, used as a basal medium, was supplemented with yeastolate, carbohydrates, amino acids and lipids aiming initially to reduce and further to eliminate the need of fetal bovine serum. The S2AcGPV2 cells were fully capable of growing in serum-free supplemented IPL-41 medium containing 6 g L(−1) yeastolate ultrafiltrate, 10 g L(−1) glucose, 3.5 g L(−1) glutamine, 0.5 g L(−1) fructose, 2 g L(−1) lactose, 0.6 g L(−1) tyrosine, 1.48 g L(−1) methionine and 1% (v/v) lipid emulsion, reaching 19 × 10(6) cells mL(−1). Maximum specific growth rate and cell productivity were 0.025 h(−1) and 0.57 × 10(5) cells mL(−1) h(−1), respectively. Glucose and lactose were consumed during cell culture, but not fructose. Lactate concentration generally decreased during cell culture, while ammonium concentration reached 167 mg L(−1), however, without noticeable deleterious effects on cell growth. GPV concentration values achieved were, however, modest in the proposed medium formulation.